2013
DOI: 10.1074/jbc.m112.443267
|View full text |Cite
|
Sign up to set email alerts
|

AP-1/Fos-TGase2 Axis Mediates Wounding-induced Plasmodium falciparum Killing in Anopheles gambiae

Abstract: Background: Wounding renders mosquitoes resistant to human malaria parasites. Results: Genome-wide transcriptional profiling identified 53 wound response genes, including two transglutaminases. Functional studies revealed the role of AP-1/TGase2 axis in the mosquito resistance to Plasmodium falciparum. Conclusion: AP-1/TGase2 is a new axis of the mosquito immune responses to malaria parasites. Significance: Multiple signaling pathways contribute to mosquito resistance to malaria and represent new potential tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 62 publications
(63 reference statements)
3
32
0
Order By: Relevance
“…Similar to the suggested role of hemocytes in Drosophila (33, 34), mosquito hemocyte differentiation may promote a wound-healing response that in turn negatively influences parasite survival. In support of this hypothesis, genes involved in wound healing have been implicated in P. falciparum killing (35). Alternatively, we cannot exclude that oocyst recognition may itself trigger hemocyte differentiation.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to the suggested role of hemocytes in Drosophila (33, 34), mosquito hemocyte differentiation may promote a wound-healing response that in turn negatively influences parasite survival. In support of this hypothesis, genes involved in wound healing have been implicated in P. falciparum killing (35). Alternatively, we cannot exclude that oocyst recognition may itself trigger hemocyte differentiation.…”
Section: Discussionmentioning
confidence: 79%
“…Recently AP-1 was demonstrated to be a key mediator of anti-plasmodial immunity in An. gambiae (Garver et al, 2013;Nsango et al, 2013). Our results show that the binding efficiency of the AP-1 motif of As-pro-PO V with the nuclear extract of Ar.…”
Section: Discussionmentioning
confidence: 67%
“…This is not surprising given that the JNK pathway is a well-known regulator of wounding responses in Drosophila [12] and midgut invasion by ookinetes entails considerable damage to midgut cells [13]. Consistently, other studies revealed a link between wounding and antiparasitic responses [14][15][16][17]. Indeed, within the first 3 h after wounding, the wounding-responsive AP1 factor Fos induces expression of a group of genes involved in wound healing, including the transglutaminase 2 (TGase2).…”
Section: Cellular and Molecular Responses To Plasmodium Infectionmentioning
confidence: 72%
“…TGase 2 has been associated with coagulation, and it stimulates P. falciparum killing in An. gambiae [16]. The mechanisms of tissue-specific wounding responses remain unclear in An.…”
Section: Cellular and Molecular Responses To Plasmodium Infectionmentioning
confidence: 99%